2021
DOI: 10.3389/fevo.2021.733023
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory System Morphology Suggests Colony Size Drives Trait Evolution in Odorous Ants (Formicidae: Dolichoderinae)

Abstract: In social insects colony fitness is determined in part by individual worker phenotypes. Across ant species, colony size varies greatly and is thought to affect worker trait variation in both proximate and ultimate ways. Little is known about the relationship between colony size and worker trait evolution, but hypotheses addressing the role of social structure in brain evolution suggest workers of small-colony species may have larger brains or larger brain regions necessary for complex behaviors. In previous wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 114 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…For example, antennal lobe glomeruli are close proxies of underlying olfactory receptor function, and subspecialization of this system reflects olfactory adaptation [77]. Volumes of each glomerulus as well as glomeruli number thus closely mirror investment in synaptic numbers and receptor diversity, making volume and number accurate proxies [78][79][80]. However, even in this case, any investment in increased glomerulus size or overall number needs to be placed into the context of the overall olfactory circuit.…”
Section: Overarching Themes: Evolvability and Modularitymentioning
confidence: 99%
“…For example, antennal lobe glomeruli are close proxies of underlying olfactory receptor function, and subspecialization of this system reflects olfactory adaptation [77]. Volumes of each glomerulus as well as glomeruli number thus closely mirror investment in synaptic numbers and receptor diversity, making volume and number accurate proxies [78][79][80]. However, even in this case, any investment in increased glomerulus size or overall number needs to be placed into the context of the overall olfactory circuit.…”
Section: Overarching Themes: Evolvability and Modularitymentioning
confidence: 99%
“…Secondly, it has been demonstrated that functional ORs are necessary for non‐nestmates discrimination in Camponotus floridanus (Ferguson et al ., 2020). Accordingly, the transition to higher social complexity may be associated with expansions of brain regions supporting olfactory communication, as has been observed between ant species with different colony sizes (Riveros, Seid & Wcislo, 2012; Godfrey et al ., 2021). This idea is also supported by observations made in Halictidae (sweat bees), in which a higher investment in chemosensory structures on the antennae has been observed in social bees compared to solitary ones, at both species and population levels (Wittwer et al ., 2017; Wenseleers & van Zweden, 2017; Boulton & Field, 2022).…”
Section: The Social Brain Hypothesis and Beyondmentioning
confidence: 99%
“…In social Hymenoptera, previous research has intensively documented the chemical signals involved in recognition and how they might reflect attributes of the signaller, but the features ensuring adequate reception of the signals and how it is enabled by receptor organs of the receiver have received much less consideration. So far, the BaS and the 9‐exon ORs have emerged as key elements of CHC detection, and they are considered as components of the nestmate recognition system in the current literature (Nishikawa et al ., 2012; Zhou et al ., 2015; McKenzie et al ., 2016; Godfrey et al ., 2021; Gellert et al ., 2022). The apparent dichotomy of the BaS subsystem with the general olfactory system conveniently allows the study of recognition at the neuronal level with little interference from the general odour‐detection system.…”
Section: Competing Evolutionary Hypotheses For the Origin Of A Specia...mentioning
confidence: 99%